2020
DOI: 10.1016/j.prnil.2020.03.004
|View full text |Cite
|
Sign up to set email alerts
|

What is the ideal number of biopsy cores per lesion in targeted prostate biopsy?

Abstract: Background The number of cores to be obtained in targeted biopsy (TB) is important. This study aimed to evaluate the TB outcomes in suspicious prostate lesions classified according to the Prostate Imaging Reporting and Data System (PI-RADS) and to determine the ideal number of biopsy cores per lesion. Methods This retrospective study included patients who underwent multiparametric magnetic resonance imaging–guided fusion prostate biopsy owing to increased serum prostate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Since MRI-targeted biopsies were performed before systematic biopsies, there is a possibility that the physician performing the systematic biopsy may have been influenced by ultrasound-visible changes when performing systematic prostate biopsies, even though attempts were made to reduce this possibility. Furthermore, while the use of two biopsy cores per MRI-visible target resulted in detection of substantially more clinically significant cancer than with systematic biopsy, some recent studies have suggested that a higher number of biopsy cores may result in an increase in the detection of clinically significant cancer [10,[34][35][36]. This study used transrectal biopsy to diagnose prostate cancer and these findings may not apply for transperineal biopsy, as a transperineal approach may provide superior access to the apical and anterior regions of the prostate.…”
Section: Discussionmentioning
confidence: 99%
“…Since MRI-targeted biopsies were performed before systematic biopsies, there is a possibility that the physician performing the systematic biopsy may have been influenced by ultrasound-visible changes when performing systematic prostate biopsies, even though attempts were made to reduce this possibility. Furthermore, while the use of two biopsy cores per MRI-visible target resulted in detection of substantially more clinically significant cancer than with systematic biopsy, some recent studies have suggested that a higher number of biopsy cores may result in an increase in the detection of clinically significant cancer [10,[34][35][36]. This study used transrectal biopsy to diagnose prostate cancer and these findings may not apply for transperineal biopsy, as a transperineal approach may provide superior access to the apical and anterior regions of the prostate.…”
Section: Discussionmentioning
confidence: 99%
“…They specified that there might also be a patient group that would benefit from more core sampling (29). Sonmez et al reported that 2 or 3 cores could be efficient for PI-RADS 4 and 5 lesions, while at least 4 cores should be obtained from PI-RADS 3 lesions (30). In our study, the mean number of cores per lesion in MRI-US FPBx was 4 (3-5) and we believe that it is sufficient for the effectiveness of our biopsy results.…”
Section: Discussionmentioning
confidence: 99%
“…Our data indicate that this approach is superior in terms of detection of clinically signi cant cancer as compared to up to three targeted biopsies (78.3% vs 67.4%). Some authors claim that two to three biopsy cores may be su cient in PI-RADS 4 and 5 lesions 15 . However, our data indicate that the application of target saturation biopsies -with a median number of 6 biopsies per lesion in this study -can reduce the number of missed cancer in a statistically signi cant manner, and can provide a more accurate characterization in terms of assigned Gleason score for PCa detected within the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…However, up to 70% of PCa lesions display intralesional tumor heterogeneity 10 , and targeted biopsy strategies do not yet adequately account for this nding, as the number of targeted biopsies varies signi cantly [11][12][13][14] and no standard has been de ned. Some authors have assessed the impact of the number of targeted biopsy per lesion 11,12,15 , and the combination of sampling the center and the periphery has been proposed 10 . However, there are no reports of targeted saturation biopsy strategies to speci cally cover a lesion comprehensively.…”
Section: Read Full License Introductionmentioning
confidence: 99%